2013
DOI: 10.1038/jid.2012.367
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation Analysis in 98 Individuals with PHACE Syndrome

Abstract: PHACE syndrome is the association of large segmental facial hemangiomas and congenital anomalies, such as posterior fossa malformations, cerebral arterial anomalies, coarctation of the aorta, eye anomalies and sternal defects. To date, the reported cases of PHACE syndrome have been sporadic suggesting that PHACE may have a complex pathogenesis. We report here genomic copy number variation (CNV) analysis in 98 individuals with PHACE syndrome as a first step in deciphering a potential genetic basis of PHACE synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…PHACE has a female predominance, although preliminary X‐inactivation studies have not demonstrated significant skewing in affected female patients or their mothers . Copy‐number variation studies have yet to identify a common pathogenic variant . We sought to determine whether there is an increased prevalence of miscarriage, infertility and/or use of in vitro fertilization (IVF) in the mothers of children with PHACE.…”
mentioning
confidence: 99%
“…PHACE has a female predominance, although preliminary X‐inactivation studies have not demonstrated significant skewing in affected female patients or their mothers . Copy‐number variation studies have yet to identify a common pathogenic variant . We sought to determine whether there is an increased prevalence of miscarriage, infertility and/or use of in vitro fertilization (IVF) in the mothers of children with PHACE.…”
mentioning
confidence: 99%
“…Although the strong female predominance suggests an X-linked inheritance, skewed X-chromosome-inactivation has been identified in only a few cases, without statistical significance [14]. A series analyzing 98 individuals with PHACE syndrome discovered 10 rare genomic copy number variations, but none of these occurred in > 1 subject [15]. The deletions on 7q33 may also provide a genetic susceptibility to PHACE syndrome, but they are not the singular cause of phenotypic expression [12].…”
Section: Discussionmentioning
confidence: 99%
“…The deletions on 7q33 may also provide a genetic susceptibility to PHACE syndrome, but they are not the singular cause of phenotypic expression [12]. This suggests that PHACE syndrome may have a complex pathogenesis and likely genetic heterogenicity, while an X-linked gene mutation is possibly associated with a subset of occurrence [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…No specific mutation was identified for these syndromes; however, genomic copy number variation has been found in PHACE syndrome. 37 Vascular endothelial growth factor (VEGF) and VEGF receptors Several signalling pathways have been linked with IH pathogenesis, with the VEGF-A pathway being the key one. VEGF-A is a master regulator of angiogenesis and vasculogenesis.…”
Section: Molecular Basis Of Infantile Haemangioma Geneticsmentioning
confidence: 99%